Spectrophotometric studies on some arylazo diamino pyrimidinol in organic solvents and in buffer solutions - Abdalla, Nadia Ahmed; El-Haty, Mohamed Tawfek; Adam, Farok Abd-Elkarim; Hassan, Fatma Wafdy (European Journal of Chemistry, 2014)
The spectral behavior of some new arylazo-2,6-diamino-4-pyrimidinol in pure and mixed organic solvents and buffer solutions of varying pH have been studied. The observed bands are assigned to the possible electronic transition. The band appearing in the visible region is assigned to p→p* transition involving p-electronic system of the whole compounds, associated with intramolecular charge transfer. This charge transfer seems to originate from the aryl moiety to the pyrimidine ring which is characterized by accepting character. This behavior can be explained that these compounds exist in the hydroxyazo-quinoid hydrazon tautomreic explained equilibrium. The possibility of the formation of a-H-bond solvated molecular complex between the molecule of azo 2,6-diaminopyrimidinol and proton-acceptor solvents of DMSO and DMF molecular were discussed. The pK values of these compounds were determined and on the basis of the relative contribution of acidic basic character of respective species.